2017
DOI: 10.18632/oncotarget.16771
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perioperative blood transfusion on clinical outcomes in patients with colorectal liver metastasis after hepatectomy: a meta-analysis

Abstract: BACKGROUNDPerioperative blood transfusion may be associated with negative clinical outcomes in oncological surgery. A meta-analysis of published studies was conducted to evaluate the impact of blood transfusion on short- and long-term outcomes following liver resection of colorectal liver metastasis (CLM).MATERIALS AND METHODSA systematic search was performed to identify relevant articles. Data were pooled for meta-analysis using Review Manager version 5.3.RESULTSTwenty-five observational studies containing 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 37 publications
1
32
0
1
Order By: Relevance
“…A recent meta-analysis by Lyu et al[9] examined the outcomes of patients who received a hepatectomy for CRC metastasis. The analysis included 10621 patients, and the authors found that transfused patients had higher overall morbidity (OR = 1.98), higher mortality (OR = 4.13), longer hospital stays (OR = 4.43), reduced overall survival (RR = 1.24), and reduced disease-free survival (RR = 1.38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis by Lyu et al[9] examined the outcomes of patients who received a hepatectomy for CRC metastasis. The analysis included 10621 patients, and the authors found that transfused patients had higher overall morbidity (OR = 1.98), higher mortality (OR = 4.13), longer hospital stays (OR = 4.43), reduced overall survival (RR = 1.24), and reduced disease-free survival (RR = 1.38).…”
Section: Discussionmentioning
confidence: 99%
“…However, these patients are at an increased risk for a perioperative transfusion, and thus the effect of a transfusion on surgical and oncological outcomes is an area of study. A number of studies have indicated that patients with CRC undergoing colon resection and/or surgical treatment of liver metastasis who receive a perioperative allogeneic transfusion have increased mortality, reduced overall survival, reduced disease free survival, more postoperative complications, and longer length of hospital stay[4,9-12]. Studies, however, have not been consistent in all of their findings.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a lower Hb-value was recently reported by our center as negative predictor for survival [ 18 ]. Furthermore, a lower Hb-value might cause an increased need for perioperative blood transfusion, lately reported to impair disease-free and overall survival [ 19 , 20 ]. The Quick's value in % was not described previously as prognostic factor in liver resection for colorectal liver metastases but it appears logical that a higher value correlates with a better synthetic function of the organ and a more stable function of the liver remnant after resection.…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia may shorten survival time in cancer patients and worsen local tumour control . In addition, meta‐analyses in different types of cancer show that red cell transfusions increase the risk of tumour recurrence and decrease survival rates . Pre‐operative anaemia in patients for colorectal cancer surgery is common (30–67%) and is a cause for concern .…”
Section: Who?mentioning
confidence: 99%